2006
DOI: 10.1002/art.21912
|View full text |Cite
|
Sign up to set email alerts
|

Transition from primary Raynaud's phenomenon to secondary Raynaud's phenomenon identified by diagnosis of an associated disease: Results of ten years of prospective surveillance

Abstract: Objective. To assess the early signs, risk factors, and rate of transition from primary Raynaud's phenomenon (primary RP) to secondary RP.Methods. A clinical sample of 307 consecutive patients with RP was included in a prospective followup study. After an initial screening, 244 patients were classified as having primary RP, of whom 236 were followed up for a mean ؎ SD of 11.2 ؎ 3.9 years. Patients classified according to the screening as having suspected secondary RP underwent an extended screening program ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(73 citation statements)
references
References 27 publications
3
61
0
6
Order By: Relevance
“…In the study by Hirschl et al (1), the initial prevalence of secondary RP following the extended screening program was 11%; however, during the followup period of 11.2 Ϯ 3.9 years, the prevalence shifted to 14.9%. In our investigation, following careful analysis by nailfold videocapillaroscopy, a similar prevalence of secondary RP (14.6%) was identified, but after a much shorter followup period (29.4 Ϯ 10 months).…”
Section: To the Editormentioning
confidence: 93%
See 1 more Smart Citation
“…In the study by Hirschl et al (1), the initial prevalence of secondary RP following the extended screening program was 11%; however, during the followup period of 11.2 Ϯ 3.9 years, the prevalence shifted to 14.9%. In our investigation, following careful analysis by nailfold videocapillaroscopy, a similar prevalence of secondary RP (14.6%) was identified, but after a much shorter followup period (29.4 Ϯ 10 months).…”
Section: To the Editormentioning
confidence: 93%
“…We read with interest the report by Hirschl et al on transition from primary to secondary Raynaud's phenomenon (RP) identified by diagnosis of an associated disease (1). The generally accepted criteria for primary RP include symmetric attacks; absence of tissue necrosis, ulceration, or gangrene; absence of a secondary cause (based on medical history and physical examination); absence of antinuclear antibodies; normal erythrocyte sedimentation rate; and, of interest, presence of normal nailfold capillaries (2).…”
Section: To the Editormentioning
confidence: 99%
“…Other studies reported that 15-20% of patients initially diagnosed as affected by primary RP transitioned to secondary RP over a mean follow-up of 2 years [31] and [32].…”
Section: Secondary Rpmentioning
confidence: 99%
“…Occurring in more than 90% of patients, RP often precedes skin and visceral fibrosis by years or decades (2). Hence, at initial presentation of RP, there is a need for novel predictors to help physicians in identifying the patients who are at risk of developing SSc or another connective tissue disease (CTD) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%